Current Practices Regarding Treatment of Neonatal Jaundice by Neonatal Care Practitioners in Nigeria - Beatrice Ezenwa; Yeside Akinbolagbe; Iretiola Fajolu; Patricia Akintan; Luther Agaga; Veronica Ezeaka (Mashhad University of Medical Sciences, 2018)
Background: Neonatal jaundice is a common medical condition encountered in the neonatal period in Nigerian hospitals. Its management is not homogenous among healthcare providers. Therefore, this study aimed at evaluating current practices related to the treatment of neonatal jaundice among doctors and nurses caring for neonates in Nigeria. Methods: Healthcare providers managing neonates in Nigeria were surveyed during annual general and scientific meetings of the Nigerian Society of Neonatal Medicine in 2017. In addition, the Paediatric Association of Nigeria's mailing list was utilized to disseminate a self-administered, pretested and structured questionnaire to doctors and nurses involved in taking care of newborns in Nigeria. Results: The results of the study showed that local guidelines / protocols were highly applied by the respondents. The majority of the health care providers would screen newborns for neonatal jaundice before discharge. The practice of early discharge within 24 hours was rampant with a high frequency of late follow up at 6 weeks. Conclusion: The practices regarding management of neonatal jaundice among healthcare professionals in Nigeria vary with better practices observed in specialist cadres. Newborn discharge and follow-up practices also vary and are sub-optimal. Therefore, there is a need for more awareness creation on neonatal jaundice treatment among cadres of health care practitioners. This should be complimented with the development of a national guideline on the management of neonatal jaundice in Nigeria.